ChemInform Abstract: Total Synthesis of a Pyrrole Lactone Alkaloid, Longanlactone. Issue 14 (April 2015) - Reddy, Chada Raji; Reddy, Motatipally Damoder; Dilipkumar, Uredi
Abstract: Key reactions in the first asymmetric total assembly of the natural pyrrole lactone longanlactone (I) are a Barbier propargylation and a Paal—Knorr pyrrole synthesis.